Pengaruh Promosi dan Distribusi Terhadap Kepuasan Pelanggan Pada PT Tiga Serangkai Internasional Cabang Bandung - Anang Martoyo; Fajar Mahardika (Universitas Pamulang, 2020)
The objectives of the research are to know the responses about promotion, distribution, customer satisfaction, and customer trust, also to analyze the influence of promotion and distribution to customer satisfaction and its implication on customer trust. The population in this study is PT. Tiga Serangkai International in the reater Bandung Region. The research method used in this research is descriptive and verification research method with a sample size of 90 respondents, data collection by interview using a questionnaire, observation and literature. Sampling technique using the